2020
DOI: 10.3390/ijerph17134811
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Psychotherapy during the COVID-19 Pandemic among Czech, German and Slovak Psychotherapists

Abstract: Psychotherapists around the world are facing an unprecedented situation with the outbreak of the novel coronavirus disease (COVID-19). To combat the rapid spread of the virus, direct contact with others has to be avoided when possible. Therefore, remote psychotherapy provides a valuable option to continue mental health care during the COVID-19 pandemic. The present study investigated the fear of psychotherapists to become infected with COVID-19 during psychotherapy in personal contact and assessed how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
0
16

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 32 publications
6
80
0
16
Order By: Relevance
“…A similar reduction in psychotherapy was observed in Austria, where a decline in face-to-face sessions was compensated by a reported increase in telepsychotherapy in the early weeks of the COVID-19 lockdown -even though the increase was not sufficient to cover the full proportion of interrupted treatments (Probst et al, 2020). On the contrary, a survey study conducted in the Czech Republic, Germany, and Slovakia did not observe psychotherapy dropout during the pandemic (Humer et al, 2020). Notably, the present study was conducted during the peak of the pandemic, after the Italian government imposed strong limitations on personal movement; in contrast, no curfews existed in the aforementioned survey study at the time of data collection (Humer et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A similar reduction in psychotherapy was observed in Austria, where a decline in face-to-face sessions was compensated by a reported increase in telepsychotherapy in the early weeks of the COVID-19 lockdown -even though the increase was not sufficient to cover the full proportion of interrupted treatments (Probst et al, 2020). On the contrary, a survey study conducted in the Czech Republic, Germany, and Slovakia did not observe psychotherapy dropout during the pandemic (Humer et al, 2020). Notably, the present study was conducted during the peak of the pandemic, after the Italian government imposed strong limitations on personal movement; in contrast, no curfews existed in the aforementioned survey study at the time of data collection (Humer et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…On the contrary, a survey study conducted in the Czech Republic, Germany, and Slovakia did not observe psychotherapy dropout during the pandemic (Humer et al, 2020). Notably, the present study was conducted during the peak of the pandemic, after the Italian government imposed strong limitations on personal movement; in contrast, no curfews existed in the aforementioned survey study at the time of data collection (Humer et al, 2020). This mismatch in the study conditions substantially limits our ability to compare findings.…”
Section: Discussionmentioning
confidence: 63%
“…Although providing psychotherapy via telephone or internet (teletherapy) is possible ( Whaibeh et al, 2020 ; Wright and Caudill, 2020 ), many state that face-to-face contact is an essential part of the therapy ( Connolly et al, 2020 ). Thus, the required reduction of face-to-face contacts might lead to a reduced number of patients ( Humer et al, 2020 ; Probst et al, 2020 ) as some reservations against teletherapy have been shown in psychotherapists ( Schuster et al, 2018 ) and the general population ( Apolinário-Hagen et al, 2018 ). This situation might reinforce distress and job anxiety in psychotherapists, especially in those not used to provide teletherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative overload was also high, due to a lack of knowledge and high uncertainty about the virus and routes of infection, treatments, and the severity of the effects and consequences [ 15 ]. There were severe emotional demands due to the fear of infection and concern about being a potential carrier of the virus to their own family [ 16 ], as well as demands in dealing with people who are dying [ 14 , 15 , 17 ]. The stress was exacerbated by a shortage of resources.…”
Section: Introductionmentioning
confidence: 99%